Kirsten Sand's Own House, detail model (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2024)
Experimental house architect Kirsten Sand has built for herself, after she moved to Tromsø to work on the reconstruction of the area after World War II.